Design Simulation and Preparation of White OLED Microdisplay Based on Microcavity Structure Optimization - Duan, Liangfei; Wang, Guanghua; Duan, Yu; Lei, Denglin; Qian, Fuli; Yang, Qiming (Journal of Spectroscopy, 2021)
White-light OLED devices play an important application in information display fields. Optical interference of the microcavity structure has an important effect on device performances. According to the design of the band structure, ITO/MoO3 composite films were used as the anode, and Mg : Ag (1%) composite films were prepared by coevaporation as the translucent cathode; CuPc was used as the hole injection layer and anode passivation layer, NPB as the hole transmission layer and yellow light main material, rubrene as yellow dopant material, ADN as blue light main material, DSA-Ph as blue dopant material, and TPBi and Alq3 as the electron transport layers. We realized the change of the microcavity structure by adjusting the thickness of each organic functional layer film and simulated and calculated the optimized thickness of each organic film layer and influence on OLED device performances using the SimOLED software system. The optimized OLED microdisplay structure is Si(CMOS)/ITO (35 nm)/MoO3 (2 nm)/CuPc (5 nm)/2-TNATA (20 nm)/NPB (10 nm)/NPB : rubrene (1.5%)ADN : DSA-Ph (5%) (25 nm)/TPBi (15 nm)/Alq3 (1.2 nm)/Mg (13 nm) : Ag (1%). The optimized OLED microdisplay was prepared by the vacuum coating system, and the photoelectric performances of the OLED device were characterized by a spectral testing system consisting of the Photo Research PR655 spectrometer and Keithley 2400 program-controlled power supply. The effect of the microcavity structure on OLED device performances was studied. The results show that the variation of the film thickness of each organic functional layer has an important effect on the performances of OLED microdisplay, such as brightness and color coordinate, and the OLED microdisplay reaches a higher brightness of 3342 cd/m2 under the normal working voltage at 5.0 V after the structure is optimized, with CIE coordinate (0.28, 0.37), which is closer to the energy point of standard white light.